Pengaruh kepuasan kerja dan budaya organisasi terhadap komitmen organisasi karyawan - Ellys Ellys; Mei Ie (Jurnal Manajemen Maranatha, 2020)
Job satisfaction is a feeling of pleasure or disappointed employees at work or the company and organizational culture are values ??or norms that are instilled by the company. These two important variables explain organizational commitment in the form of employee desires to maintain its membership in the company. The main purpose of this study is to find out the effect of job satisfaction and organizational culture on employee organizational commitment. The sample of this research was 50 respondents, who are employees in non-managerial positions. Sampling was done by non-probability sampling with purposive sampling. The data analysis method used by researchers was PLS-SEM with bootstrapping method. The results of this study indicated that job satisfaction has a positive effect on organizational commitment and organizational culture has a positive effect on organizational commitment.